2021
DOI: 10.1093/pubmed/fdaa236
|View full text |Cite
|
Sign up to set email alerts
|

Retention and motivation of health workers in remote and rural areas in Cross River State, Nigeria: a discrete choice experiment

Abstract: Background Cross River State is making investments geared towards ensuring equitable distribution and improved retention of its frontline health workforce in remote and rural areas. This informed the conduct of a discrete choice experiment to determine the motivating factors supporting the retention of healthcare workers. Methods Study participants were 198 final year students of nursing, midwifery and community health and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 9 publications
0
24
1
3
Order By: Relevance
“…The ndings of our study place a low utility on salary despite the literature indicating that an increase in salaries is important [32] and it often causes strike actions in Nigeria's health sector [16]. Studies have also shown that salaries and other factors including those bothering on working conditions are often implied in instances of unrest [11].…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…The ndings of our study place a low utility on salary despite the literature indicating that an increase in salaries is important [32] and it often causes strike actions in Nigeria's health sector [16]. Studies have also shown that salaries and other factors including those bothering on working conditions are often implied in instances of unrest [11].…”
Section: Discussioncontrasting
confidence: 60%
“…The current situation in Nigeria indicates that health workers are not motivated and this is negatively impacting their performance and e ciency. Several factors, including poor remuneration, inadequate sta ng levels with resultant high workloads, lack of social amenities, poor working environments, inadequate medical supplies and equipment, and delayed salaries and emoluments payment have been documented [8][9][10][11][12][13][14][15][16][17]. Additionally, institutionalized attraction, retention, posting, and motivation mechanisms are absent, especially for primary level facilities often located in rural and remote areas [6,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These additional workloads are contributing to reported high workloads in the primary level of care and are considered by health workers when they plan to take up or stay in rural postings. 10,11,[22][23][24] Government should therefore put measures in place to ensure that there is an appropriate skill-mix of health workers to perform these functions.…”
Section: Journal Of Global Health Reportsmentioning
confidence: 99%
“…[7][8][9] Health workers are facing poor remuneration, high workloads, poor working environments, inadequate medical supplies and equipment, and delayed payment of salaries and emoluments. 7,[10][11][12] The weak health governance mechanism compounded by inadequate numbers of health workers at the primary level of care, the entry point into Nigeria's health system, necessitates the need to ensure that staffing levels are informed by workloads. This study utilized the Workload Indicator for Staffing Needs (WISN) method 8 to determine the staffing needs in selected facilities in Cross Rivers State of Nigeria.…”
mentioning
confidence: 99%